B cells are critical for autoimmune pathology in Scurfy mice - Aschermann, Susanne (National Academy of Sciences, 2013)
Impaired regulatory T-cell function results in a severe chronic autoimmune disease affecting multiple organs in Scurfy mice and humans with the immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX) syndrome. Previous studies have shown that T helper cells but not cytotoxic T cells are critical for the disease pathology. Whether this T-cell subset is responsible directly for tissue inflammation or rather indirectly via the interaction with B cells or myeloid cells is largely unknown. To study this and to identify potential therapeutic targets for this lethal disease we investigated the contribution of B cells to this complex autoimmune phenotype. We show that B cells and the production of autoantibodies plays a major role for skin, liver, lung, and kidney inflammation and therapeutic depletion of B cells resulted in reduced tissue pathology and in prolonged survival. In contrast, the absence of B cells did not impact systemic T-cell activation and hyperreactivity, indicating that autoantibody production by B cells may be a major factor for the autoimmune pathology in mice deficient for regulatory T cells.